Interaction between Orobanche crenata and its Host Legumes: Unsuccessful Haustorial Penetration and Necrosis of the Developing Parasite - PÉREZ-DE-LUQUE, A. (Ann Bot, 2005)
• Background and Aims Orobanche species represent major constraints to crop production in many parts of the world as they reduce yield and alter root/shoot allometry. Although much is known about the histology and effect of Orobanche spp. on susceptible hosts, less is known about the basis of host resistance to these parasites. In this work, histological aspects related to the resistance of some legumes to Orobanche crenata have been investigated in order to determine which types of resistance responses are involved in the unsuccessful penetration of O. crenata. • Methods Samples of resistance reactions against O. crenata on different genotypes of resistant legumes were collected. The samples were fixed, sectioned and stained using different procedures. Sections were observed using a transmission light microscope and by epi-fluorescence. • Key Results Lignification of endodermal and pericycle host cells seems to prevent parasite intrusion into the root vascular cylinder at early infection stages. But in other cases, established tubercles became necrotic and died. Contrary to some previous studies, it was found that darkening at the infection site in these latter cases does not correspond to death of host tissues, but to the secretion of substances that fill the apoplast in the host–parasite interface and in much of the infected host tissues. The secretions block neighbouring host vessels. This may interfere with the nutrient flux between host and parasite, and may lead to necrosis and death of the developing parasite. • Conclusions The unsuccessful penetration of O. crenata seedlings into legume roots cannot be attributed to cell death in the host. It seems to be associated with lignification of host endodermis and pericycle cells at the penetration site. The accumulation of secretions at the infection site, may lead to the activation of xylem occlusion, another defence mechanism, which may cause further necrosis of established tubercles.